2012
DOI: 10.1097/prs.0b013e3182362010
|View full text |Cite
|
Sign up to set email alerts
|

Nonactivated versus Thrombin-Activated Platelets on Wound Healing and Fibroblast-to-Myofibroblast Differentiation In Vivo and In Vitro

Abstract: Platelets stimulate wound healing more efficiently compared with activated platelets by enhancing fibroblast differentiation and contractile function. Similar levels of growth factors may induce different biological effects when delivered "on demand" rather than in an initial bolus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 22 publications
0
76
0
2
Order By: Relevance
“…57 There is also evidence that PLTs without preactivation stimulate wound healing more efficiently than preactivated PLTs. 58 Indeed, positive clinical results in knee OA have been reported in PRP injections both with and without PLT preactivation. 25,40,44,50,51,59 To date, there are no clinical trials comparing different types of PRP activation.…”
Section: Plt Preactivationmentioning
confidence: 97%
“…57 There is also evidence that PLTs without preactivation stimulate wound healing more efficiently than preactivated PLTs. 58 Indeed, positive clinical results in knee OA have been reported in PRP injections both with and without PLT preactivation. 25,40,44,50,51,59 To date, there are no clinical trials comparing different types of PRP activation.…”
Section: Plt Preactivationmentioning
confidence: 97%
“…However, rendering mice thrombocytopenic leads to increased wound inflammation without affecting the reparative aspects of wound repair (56). A recent study demonstrated better healing responses in diabetic mice injected with nonactivated versus thrombin-activated platelets; the authors concluded that platelets may be used as cell therapy rather than exploited for their growth factor content (57). The approach that we have taken preserved the cells and ablated the defined spectrum of growth factors specifically contained in platelet α-granules.…”
Section: Figurementioning
confidence: 99%
“…Numerous wound dressings are in use. Topical use of autologous platelets has also been described [5]. Majority of clinical studies focus on defects classified as Wagner/Armstrong stadium 1 and 2.…”
Section: Introductionmentioning
confidence: 99%